Research and Application of Milling Parameters Optimization Based on Genetic Algorithm - Yuan, Sheng Wan; Zhang, Yu; Hu, Min Min (Advanced Materials Research, 2015)
At present a number of machinery factories select cutting parameters mainly rely on the experience in China. In order to get the reasonable cutting parameters and then have a optimal machining surface quality, high production efficiency and low production cost. In this paper, using genetic algorithm and Matlab software [1] to optimize cutting parameters of milling and combining with the actual cutting test in factory to verify the optimized data. And then provide theory basis and feasible measure for milling.